Exploring the Education Mismatch: A Phenomenological Study of Technology and Livelihood Education (TLE) Teachers Assigned Outside Specialization - John Paul C. Demapendan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study investigates the experiences, challenges, job performance, financial and professional impact, coping strategies, and perceptions of Technology and Livelihood Education (TLE) teachers who are assigned outside their area of specialization. Methodology: This study utilized a phenomenological approach. Twelve public school TLE (Technology and Livelihood Education) teachers were purposively selected based on their years of teaching outside their specialization and their willingness to participate. The data collection technique included the profiling of participants and the use of open-ended questions designed to elicit detailed descriptions of the participants’ experiences, challenges, and coping strategies. The data gathered from the interview sessions and written responses were transcribed and thematically analyzed to identify emerging themes. Main Findings: The findings indicate that TLE teachers are often assigned to subjects like Filipino, MAPEH (Music, Arts, Physical Education, and Health), Values Education, Social Studies, English, and Science, mainly covering MAPEH and Filipino. This leads to challenges such as anxiety and questions about pursuing further education, hindering their professional growth. While the financial impact is negligible due to the provided materials, the mismatch affects teaching performance and student trust. Teachers often collaborate, use multimedia, and engage in self-directed learning to cope. Novelty/Originality of this study: This study presents a comprehensive analysis of how TLE teachers teaching outside of specialization impact the quality of education provided to students. It recommends implementing free retooling programs, offering scholarship grants, and providing teacher training. The study emphasizes the need for teachers to teach within their specialization and for strengthening community partnerships to address the shortage of specialized educators.